Development of Culinary Tourism Using Community Based Tourism Perspective in Pangkal Pinang, Bangka Belitung - Indra, Febryola (Journal of Industrial Engineering & Management Research, 2021)
The purpose of this study is to determine (1) the application of Culinary CBT principles in Bangka Belitung focus in Pangkal Pinang; (2) conformity between its management and the criteria for implementing CBT, and (3) its development efforts. This study uses a qualitative descriptive approach. Type this research is a case study on the management of the Pangkal Pinang Culinary Tourism. With data collection techniques through interviews, observation and documentation. The results showed that (1) Pangkal Pinang has applied CBT principles in economic, social, cultural, politics, and the environment. On indicators of respect for different cultures yet maximum because the local community has not been open to visitors and has not cultural attractions. Indicators of increasing power have not materialized due to POKDARWIS focuses on community assistance; (2) Pangkal Pinang Culinary Tourism in accordance with the CBT criteria, namely getting community support, economic benefits and tourism protect culture and environment; (3) has shown progress in terms of the quantity of infrastructure facilities as well as service quality. However, the availability of clean water, rest areas, cafes and lodging is still under standard. Keywords — Culinary Tourism, Community Based Tourism (CBT), Pangkal Pinang.